1968
DOI: 10.1002/macp.1968.021120101
|View full text |Cite
|
Sign up to set email alerts
|

Ceric ion‐reducing agent redox initiated vinyl polymerisation

Abstract: Ceric perchlorate/formaldehyde (F)redox couple initiated polymerisation of the monomer methyl acrylate (MA), acrylonitrile (AN), and methyl methacrylate (MMA) in perchloric acid (25OC) was carried out. The rate of polymerisation was directly proportional to [MI2 and [F] for all the systems. The rate was independent of [Ce4+] for the systems with MA or AN, but inversely proportional to [Ce4+] with MMA as the monomer. The rate of ceric disappearance was directly proportional to [Ce4+], [F], and [MI. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1972
1972
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Applying the steady-state principle to the primary radicals R° and the growing polymeric radicals RMn° and making the usual assumption that the radical reactivity is independent of radical size 7…”
Section: → °+°mentioning
confidence: 99%
See 1 more Smart Citation
“…Applying the steady-state principle to the primary radicals R° and the growing polymeric radicals RMn° and making the usual assumption that the radical reactivity is independent of radical size 7…”
Section: → °+°mentioning
confidence: 99%
“…According to the complex mechanism, unimolecular disproportionation of complex yields a cerrous ion, a proton, and a free radical on the alcohol substrate 2,3 . Ce(IV) ion either alone or in combination with various organic reducing agents such as alcohols 4 , acids 5 , amides 6 , aldehydes 7 and ketones 8 has been used to initiate vinyl polymerization. The polymerization of acrylonitrile by Ce(IV)-glucose system was studied by Padhi and Singh 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that polymerizations of vinyl monomers are initiated by system consisting of ceric ion and a reducing agent such as alcohols [12], aldehydes [13], and amines [14]. Ceric ion/alcohol systems have been used for the graft polymerization of vinyl monomers to polymers having hydroxyl groups [ 151.…”
Section: Initiation Of Polymerization By Ceric Lon/baso-hs Systemmentioning
confidence: 99%
“…The decrease in conversion of acrylamide by nitric acid is caused by the decrease in value of K, as well as increase k;, for ceric salt will become more reactive with the aid of the acid. SUBRAMANIAN et al 15) reported the reduction of degree of polymerization on acrylonitrile. The similar consideration was previously reported by MINO et al 12).…”
Section: Effect Of Nitric Acid On Propagationmentioning
confidence: 99%